Cultural Attachment: From Behavior to Computational Neuroscience - Yap, Wei-Jie; Cheon, Bobby; Hong, Ying-yi; Christopoulos, George I. (Frontiers in Human Neuroscience, 2019)
Cultural attachment (CA) refers to processes that allow culture and its symbols to provide psychological security when facing threat. Epistemologically, although we currently have an adequate predictivist model of CA, it is necessary to prepare for a mechanistic approach that will not only predict, but also explain CA phenomena. Towards that direction, we first examine the concepts and mechanisms that are the building blocks of both prototypical maternal attachment and CA. Based on existing robust neuroscience models we associate these concepts and mechanisms with bona fide neurobiological functions to advance an integrative neurobiological model of CA. We end by discussing the unresolved relationship of CA to other similar socio-cognitive concepts. The aim of the paper is to highlight the importance of integrating CA theory into computational approaches to culture and evolution (such as predictive processing computations explaining niche construction) as this will allow a dynamic interpretation of cultural processes.